Development of a self-help digital intervention for young people with Tourette syndrome - Babbage, Camilla (2021)
Young people (YP) with Tourette Syndrome (TS) and Tic Disorders (TD) experience difficulties with psychological wellbeing and reduced quality of life (QoL). Nonetheless, accessing healthcare support for these YP is difficult due to barriers including a lack of healthcare professionals, low healthcare coverage and reduced help-seeking behaviour of YP. Current psychological interventions for people with tics do not show the cost-savings or effectiveness to substantiate large-scale implementation. Interventions delivered digitally, utilising a self-help approach may overcome these limitations and have been shown to be effective in YP with mental health difficulties. Furthermore, the development of a wellbeing intervention using person, evidence and theory-based approaches could promote adherence and engagement to such an intervention. The current research aims to develop a digital self-help intervention to support and promote psychological wellbeing in YP with TDs. A person-based approach (PBA) was applied throughout. The research included a systematic review to assess similar interventions that were available for YP with TDs and YP with reduced psychological wellbeing. Qualitative research methods were used to interview YP with TDs, professionals who work with YP with TDs, and focus groups with parents and YP with TDs to explore what would be needed from such an intervention. Thematic analysis was used to code data inductively and a hybrid thematic analytical approach was used to apply deductive analysis to the data. The findings from across the methods were integrated to develop guiding principles and a logic model to support the future development of the intervention. The systematic review identified 985 studies, leaving 11 to be included in the review. Across the qualitative methods, 16 professionals, 51 YP and 35 parents or caregivers were recruited for interviews or focus groups. A digital health intervention (DHI) that would be suitably applied to YP with tics was not identified in the literature, and it was concluded that such an intervention would be desired by YP and thought useful by professionals. Many features and functions of the intervention were highlighted across participant groups, and the most important features were prioritised. These were combined with theory to develop guiding principles and a logic model. The research outputs include the development of guiding principles and a logic model, informed using the PBA, behaviour change theory and evidence. These findings will support future developers in creating an engaging and effective intervention for YP with tics, to promote and support their wellbeing.